Different but equal: the implausible assumption at the heart of neutral theory. - Purves, D; Turnbull, L (2010)
1. The core assumption of neutral theory is that all individuals in a community have equal fitness regardless of species, and regardless of the species composition of the community. But, real communities consist of species exhibiting large trait differences; hence these differences must be subject to perfect fitness-equalizing trade-offs for neutrality to hold. 2. Here we explain that perfect equalizing trade-offs are extremely unlikely to occur in reality, because equality of fitness among species is destroyed by: (i) any deviation in the functional form of the trade-off away from the one special form that gives equal fitness; (ii) spatial or temporal variation in performance; (iii) random species differences in performance. 3. In the absence of the density-dependent processes stressed by traditional niche-based community ecology, communities featuring small amounts of (i) or (ii) rapidly lose trait variation, becoming dominated by species with similar traits, and exhibit substantially lower species richness compared to the neutral case. Communities featuring random interspecific variation in traits (iii) lose all but a few fortuitous species. 4. Thus neutrality should be viewed, a priori, as a highly improbable explanation for the long-term co-occurrence of measurably different species within ecological communities. In contrast, coexistence via niche structure and density dependence, is robust to species differences in baseline fitness, and so remains plausible. 5. We conclude that: (i) co-occurring species will typically exhibit substantial differences in baseline fitness even when (imperfect) equalizing trade-offs have been taken into account; (ii) therefore, communities must be strongly niche structured, otherwise they would lose both trait variation and species richness; (iii) nonetheless, even in strongly niche-structured communities, it is possible that the abundance of species with similar traits are at least partially free to drift.